KEMAMPUAN BERPIKIR KRITIS MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA PELAJARAN IPS SISWA KELAS IV SEKOLAH DASAR (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
The purpose of this study is to improve the ability to think critically through problem-based learning models in social studies class IV Elementary School. This research uses the Action Research model by choosing the Kemmis and Mc Tanggart models, namely planning (planning), acting (acting), observing (observing) and reflection (reflection). The subjects of class IV are Muara Kapuk 3 Public Elementary School with a total of 28 people, Penjaringan North Jakarta DKI Jakarta Province, Indonesia. Excessive research results using model based on models in learning IPS in class IV.Action Research